Linking cone penetration resistances measured in calibration chambers and the field. Issue 2 (26th April 2012) - Pournaghiazar, M.; Khalili, N.; Russell, A. R.
Abstract : Cone penetration tests (CPTs) conducted in sands in small calibration chambers may be heavily influenced by chamber sizes and boundary conditions, placing uncertainty on how results are related to those measured in the field. This article demonstrates how penetration resistances measured in chambers may be converted to equivalent field values, using a semi-analytical procedure based on a solution for spherical cavity expansion in soils of finite radial extent. Account is also given to differences in vertical stress states around the cone in the field and in chambers in a simple way. The procedure is validated using resistances measured in three sands by accurately predicting observed cone-chamber diameter ratio influences. Cone penetration tests (CPTs) conducted in sands in small calibration chambers may be heavily influenced by chamber sizes and boundary conditions, placing uncertainty on how results are related to those measured in the field. This article demonstrates how penetration resistances measured in chambers may be converted to equivalent field values, using a semi-analytical procedure based on a solution for spherical cavity expansion in soils of finite radial extent. Account is also given to differences in vertical stress states around the cone in the field and in chambers in a simple way. The procedure is validated using resistances measured in three sands by accurately predicting observed cone–chamber diameter ratio influences.